A systematic integrative literature review of the factors influencing the professionalization of midwifery in the last decade (2009–2019). (March 2022) - Prosen, Mirko
Highlights: The professionalization process is used by occupations to gain professional status. This article focuses on the factors that influenced this process in midwifery over the last decade. Despite the existence of traditional barriers to professionalization, new elements are emerging. Woman-centred care and interprofessional practise are becoming a new engine of this process. Self-awareness, self-esteem and confidence are vital in acknowledging professional role. Abstract: Background: The professionalization of midwifery is not only important for midwives themselves, but for women and society in general since professionalism is associated with high-quality services and moral and ethical standards. Aim: This systematic integrative literature review seeks to investigate the factors that have affected the professionalization of midwifery in the last decade (2009–2019). Methods: Systematic searches were conducted in EBSCO, PubMed, ScienceDirect, SAGE and the Web of Science Core Collection. Critical appraisal was conducted using the Mixed Methods Appraisal Tool (MMAT). The findings were synthesised through a thematic analysis. The PRISMA statement was used to guide the reporting. Findings: Analysis of the 20 studies included detected two main themes: professionalization barriers and professionalization opportunities. The first theme includes issues concerning power imbalance, social recognition, conflicting perspectives on childbirth, professional autonomy, work characteristics, midwifery associations, and regulation. The second theme includes opportunity issues related to woman-centred care, expansion of professional competency, interprofessional collaboration, and education. Key conclusions: Over the last decade, the midwifery profession has faced several barriers that seem to be historically entrenched in the professionalization of midwifery, yet changes in the professionalization process are visible in the shift towards elements of the 'new professionalism' that is rising to the surface during this process. Implications for practice: The findings suggest the socialisation process of midwifery candidates must focus on raising their self-awareness, self-esteem and confidence in their professional role; woman-centred care needs to be further promoted and implemented; and interprofessional collaboration should be addressed in educational programmes for all health professionals.